Principles of Distributed Systems 14th International Conference, OPODIS 2010, Tozeur, Tunisia, December 14-17, 2010. Proceedings - Lu, Chenyang; Masuzawa, Toshimitsu; Mosbah, Mohamed; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 14th International Conference on Principles of Distributed Systems, OPODIS 2010, held in Tozeur, Tunisia, in December 2010. The 32 full papers and 4 brief announcements presented were carefully reviewed and selected from 122 submissions. The papers are organized in topical sections on robots; randomization in distributed algorithms; brief announcements; graph algorithms; fault-tolerance; distributed programming; real-time; shared memory; and concurrency.
Robots -- Pattern Formation through Optimum Matching by Oblivious CORDA Robots -- RoboCast: Asynchronous Communication in Robot Networks -- Randomization in Distributed Algorithms -- Biased Selection for Building Small-World Networks -- Application of Random Walks to Decentralized Recommender Systems -- Uniform and Ergodic Sampling in Unstructured Peer-to-Peer Systems with Malicious Nodes -- Brief Announcements I -- Self-stabilizing (k,r)-Clustering in Wireless Ad-hoc Networks with Multiple Paths -- Self-stabilizing Byzantine Asynchronous Unison, -- Graph Algorithms -- Reliably Detecting Connectivity Using Local Graph Traits -- Distributed Game-Theoretic Vertex Coloring -- Constructing a Map of an Anonymous Graph: Applications of Universal Sequences -- Brief Announcements II -- Effect of Fairness in Model Checking of Self-stabilizing Programs -- A Formal Framework for Conformance Testing of Distributed Real-Time Systems -- Fault-Tolerance -- Signature-Free Broadcast-Based Intrusion Tolerance: Never Decide a Byzantine Value -- A Fault Avoidance Strategy Improving the Reliability of the EGI Production Grid Infrastructure -- Failure Detectors Encapsulate Fairness -- -Based k-Set Agreement Algorithms -- Distributed Programming -- Distributed Programming with Tasks -- SkewCCC+: A Heterogeneous Distributed Hash Table -- On the Automated Implementation of Time-Based Paxos Using the IOA Compiler -- Real-Time -- Partitioning Real-Time Systems on Multiprocessors with Shared Resources -- On Best-Effort Utility Accrual Real-Time Scheduling on Multiprocessors -- Tardiness Bounds for Global EDF with Deadlines Different from Periods -- Shared Memory -- Cache-Aware Lock-Free Queues for Multiple Producers/Consumers and Weak Memory Consistency -- An Adaptive Technique for Constructing Robust and High-Throughput Shared Objects -- Efficient Lock Free Privatization -- A Competitive Analysis for Balanced Transactional Memory Workloads -- Concurrency -- Fast Local-Spin Abortable Mutual Exclusion with Bounded Space -- Turning Adversaries into Friends: Simplified, Made Constructive, and Extended -- Quasi-Linearizability: Relaxed Consistency for Improved Concurrency -- A Token-Based Distributed Algorithm for the Generalized Resource Allocation Problem -- On the Message Complexity of Global Computations -- Optimizing Regenerator Cost in Traffic Grooming -- On Minimizing Average End-to-End Delay in P2P Live Streaming Systems -- Monotonic Stabilization -- Upper and Lower Bounds of Space Complexity of Self-Stabilizing Leader Election in Mediated Population Protocol -- Improving Space Complexity of Self-stabilizing Counting on Mobile Sensor Networks.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Computational complexity; Algebra -- Data processing; Artificial intelligence; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Software Engineering; Artificial Intelligence (incl. Robotics).; Symbolic and Algebraic Manipulation